Religion : a discovery in comics - Heer, Margreet de, 1972- (Nantier, Beall, Minoustchine, 2015)
In comic strip form, offers a look from different perspectives on the phenomenon of religion, the backgrounds and history of the five major world religions (Judaism, Christianity, Islam, Hinduism and Buddhism), and makes the point that religion is something that should unite us, not drive us apart.